LEGAL CERTAINTY OF DEBT PAYMENT OBLIGATION SUSPENSION APPLICATIONS FOR APARTMENT DEVELOPER DEBTORS - Jessica Dharmawan; Richard Chandra Adam (RADJA PUBLIKA, 2024)
This study aims to examine the legal certainty aspects of debt payment obligation petitions against apartment developer debtors. In the context of bankruptcy law, legal certainty is crucial to protect creditors' rights while also providing adequate protection for debtors experiencing financial distress. However, several issues arise regarding legal certainty in debt payment suspension petitions involving apartment developers. One example is the case of an apartment developer in the Commercial Court Decision No. 97/Pdt.Sus-PKPU/2024/PN Niaga Jkt Pst. This research explores the legal certainty surrounding the suspension of debt payment obligation petitions against apartment developer debtors, as governed by Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. The study finds that the court's decision demonstrates legal protection for debtors by taking into account factual conditions and creditors' rights. This ruling has significant implications for the development of bankruptcy law in Indonesia, particularly in resolving the debts of financially distressed apartment developers. In conclusion, legal certainty in the suspension of debt payment obligation petitions involving apartment developers must be grounded in the principle of justice, ensuring protection for all parties involved in the dispute while maintaining a balance between the rights of debtors and creditors.